2017
DOI: 10.1017/jfm.2017.452
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of oblique shock wave reflection off a water wedge

Abstract: Shock wave interaction with solid wedges has been an area of much research in past decades, but so far, very few results have been obtained for shock wave reflection off liquid wedges. In this study, numerical simulations are performed using the inviscid Euler equations and the stiffened gas equation of state to study the transition angles, reflection patterns, and triple point trajectory angles of shock reflection off solid and water wedges. Experiments using an inclined shock tube are also performed and schl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Later, the shock-tube experiment of Denet et al (2015) and the direct numerical simulations of Lodato, Vervisch & Clavin (2016 confirmed the triple-point formation of a shock reflected off a wavy wall, but did not relate the formation time to the initial perturbation size of the wall. Wan et al (2017) investigated numerically and experimentally the triple-point trajectory due to shock interaction with a water wedge. Mostert et al (2018a,b) hypothesized a sinusoidal perturbation in the Mach-number distribution for both initially flat and cylindrical shock geometry, finding that a shock curvature singularity, as a prelude to the formation of a triple point, occurs at a critical time τ c that is inversely proportional to the initial perturbation amplitude, .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the shock-tube experiment of Denet et al (2015) and the direct numerical simulations of Lodato, Vervisch & Clavin (2016 confirmed the triple-point formation of a shock reflected off a wavy wall, but did not relate the formation time to the initial perturbation size of the wall. Wan et al (2017) investigated numerically and experimentally the triple-point trajectory due to shock interaction with a water wedge. Mostert et al (2018a,b) hypothesized a sinusoidal perturbation in the Mach-number distribution for both initially flat and cylindrical shock geometry, finding that a shock curvature singularity, as a prelude to the formation of a triple point, occurs at a critical time τ c that is inversely proportional to the initial perturbation amplitude, .…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al. (2017) investigated numerically and experimentally the triple-point trajectory due to shock interaction with a water wedge. Mostert et al.…”
Section: Introductionmentioning
confidence: 99%
“…Further verification and validation simulations for water-hammer and underwater explosion driven plastic deformation and rupture of metallic plates with twophase flow and empirical cavitation modeling are given by Cirak et al (2007) and Deiterding et al (2009). Lastly, for further validation and verification, a combined numerical and experimental study on different shock wave reflection patterns, transition angles and triple point trajectory angles for oblique shock wave reflection off a water wedge at different inclination angles and for a range of shock Mach numbers is provided by Wan et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…There are many reports on simulation of droplet/shock interactions using sharp-interface and diffuse-interface approaches at subcritical conditions [39][40][41][42][43][44]. However, there are only two reports that simulate the fuel droplet-shock interaction at transcritical conditions [45,46].…”
Section: Introductionmentioning
confidence: 99%